The influence of the extraction parameters on the quality of dried sugar beet pulp - Bogdanović Branislav V.; Šereš Zita I.; Gyura Julianna F.; Sakač Marijana B.; Simović-Šoronja Dragana M.; Mišan Aleksandra Č.; Pajin Biljana S. (Hemijska Industrija, 2013)
Growing demand for better quality and cheaper products put on the need to industry to balance between the two kinds of needs, which are the reduction of production costs and to ensure a high quality product. This is the case with dried sugar beet pulp as a byproduct of sugar refining process. One of the possibilities to reduce energy consumption is savings in the process of thermal dehydration in the process of the conventional drying of pulp. Pulp drying is one third of total energy consumption in the sugar factory. Acidification of water extraction result in pulp that could be pressed better and in other hand in the juice with less non-sucrose compounds. Keeping the extraction process under certain conditions, directly affects on the quality of the extracted pulp and on effects of their further processing. This paper examines the impact of the extraction parameters of sugar from sugar beet and agents of acidification for water extraction (sulphurous acid, hydrogen peroxide) on the quality of dried sugar beet pulp. Extraction of sugar from sugar beet cossettes by hydrogen peroxide at pH 5.5 to 8.5 does not cause changes in mechanical properties of sugar beet cossettes and in water retention coefficient, but increases the brightness of dried sugar beet pulp for about 5-7 units, which solubility in water does not depend on the applied concentration of extracting agents, but increases in dependence on the duration of the extraction. Sugar beet pulp extracted at pH 11.0 has reduced strength, they are highly hydrated, and under the force they lose their shape, binding a larger amount of water thus reducing the effect of their pressing. The changes in microstructure were probably accompanied by segmenting the linear parts of macromolecules and are reflected in the increase of water retention capacity and increase the solubility of dried sugar beet pulp for two to three times. Under the same conditions of extraction, sulphurous acid produces similar but relatively mild changes in the characteristics of extracted and dried sugar beet pulp compared to conditions when hydrogen peroxide is used. From the point of the quality of the product of extraction, the most favorable results are obtained when the extraction is carried on at pH 5.5 for a period of 1 h at 70 °C, using water for extraction with sulphourus acid with the addition of 5% hydrogen peroxide. Under these conditions no significant degradation of sugar beet tissue is detected, do not change the physical, chemical and mechanical properties of the extracted pulp. But there is an average increase of lightness of dried noodles for about 7 units, which represents a significant improvement of their quality, since there is difficult to sell on the market the dried sugar beet pulp with increased colour.